Intended and unintended (sensory‐)motor coupling between the affected and unaffected upper limb in complex regional pain syndrome. (17th February 2015) - Bank, P.J.M.; Peper, C.E.; Marinus, J.; van Hilten, J.J.; Beek, P.J.
Abstract Background Motor dysfunction in complex regional pain syndrome (CRPS) has been associated with bilateral malfunction of sensory and motor circuits, which hints at abnormal coupling between the affected and the contralateral unaffected limb. In addition, clinical observations suggest that motor performance may depend on the (voluntary or automatic) context in which movements are executed. The present study aimed to examine the role of voluntary and automatic aspects of interlimb coupling in CRPS. Methods Twenty patients with unilateral chronic CRPS and 40 healthy controls performed a set of unimanual and bimanual motor tasks that differed in the degree to which intended bilateral planning, intended afference‐based error correction and unintended reflex‐like entrainment were involved. Results Stability of interlimb coordination was reduced in CRPS patients compared to controls, especially for tasks involving active control of the affected side. In CRPS patients, intended coupling between the hands (planning, error correction) was markedly impaired, whereas unintended coupling between the hands (entrainment) appeared normal. Conclusions Impaired motor control of the affected limb interfered with bimanual coordination, in particular for tasks involving voluntary (intended) as opposed to automatic (unintended) interlimb coupling. Our findings suggest inappropriate functioning of higher order centres involved in motor control of the affected limb, probably due to pain‐related processes and impaired processing of proprioceptive information. Motor function of the affected limb may benefit from intended synchronization with movements of the unaffected contralateral limb, suggesting that bilateral training may be useful in patients with unilateral CRPS.